Zero Waste -Based Fashion Design and Pattern E-Module for Increase Concern Environment - Muhdlor, Muhdlor; Sutopo, Yeri; Wahyuningsih, Sri Endah; Nurul Ihsani, Ade Novi (Universitas Negeri Semarang, 2026)
This research aim developing E-modules for Fashion Design and Patterns based on zero waste for increase understanding and concern environment. Background study based on height waste textiles produced in the learning process fashion in vocational schools, as well as Not yet availability of learning media that integrates zero waste principle systematic. The development model used is ADDIE, includes stage analysis, design, development, implementation,and evaluation. Subject study is student class XI SMK Ibu Kartini Semarang, expert materials, media experts, and fashion teachers.Instruments used covers sheet validation expert, questionnaire practicality, test results learning (pretest-posttest), and sheets observation activity students. Data analyzed using Aiken's, KR-20 reliability test, N-Gain test, homogeneity test, and t-test. Validation results show that the E-module is very suitable used (media = 0.89; material = 0.92). Practicality according to teachers and students is in the very practical category (average 89%). Effectiveness test show improvement significant with an average N-Gain of 0.72 (category high). The t-test results show difference significant between class experiment and control (sig. < 0.05). Observation activity student show improvement in the very good category (86%).In conclusion, the E-Module zero waste pattern is stated feasible, practical, and effective for increase understanding concepts, skills manufacturing pattern fashion friendly environment, as well as awareness ecological vocational school students. This media recommended for integrated in learning vocational based Independent Curriculum.